Law of the Land : Shades of Nordic Noir in an Arctic Western - Hiltunen, Kaisa (Palgrave Macmillan, 2020)
This book argues that adaptation is an underrecognized yet constitutive element of Nordic noir. In so doing, it reframes the prevailing critical view. Now celebrated for its global sweep, Nordic noir is equally a transmedial phenomenon. Nordic Noir, Adaptation, Appropriation deploys the tools of current adaptation studies to undertake a wide-ranging transcultural, intermedial exploration, adding an important new layer to the rich scholarship that has arisen around Nordic noir in recent years. peerReviewed